What does the literature mean by social prescribing? A critical review using discourse analysis. Issue 4 (11th April 2022) - Calderón‐Larrañaga, Sara; Greenhalgh, Trish; Finer, Sarah; Clinch, Megan
Abstract: Social prescribing (SP) seeks to enhance the role of the voluntary and community sector in addressing patients' complex needs in primary care. Using discourse analysis, this review investigates how SP is framed in the scientific literature and explores its consequences for service delivery. Theory driven searches identified 89 academic articles and grey literature that included both qualitative and quantitative evidence. Across the literature three main discourses were identified. The first one emphasised increasing social inequalities behind escalating health problems and presented SP as a response to the social determinants of health. The second one problematised people's increasing use of health services and depicted SP as a means of enhancing self‐care. The third one stressed the dearth of human and relational dimensions in general practice and claimed that SP could restore personalised care. Discourses circulated unevenly in the scientific literature, conditioned by a wider political rationality which emphasised individual responsibility and framed SP as 'solution' to complex and contentious problems. Critically, this contributed to an oversimplification of the realities of the problems being addressed and the delivery of SP. We propose an alternative 'care‐based' framing of SP which prioritises (and evaluates) holistic, sustained and accessible practices within strengthened primary care systems.